(untitled) (مجلة الواحات للبحوث والدراسات, 2026)
Digital citizenship has gained growing attention in contemporary sociology due to the digital revolution and the rapid advancement of communication technologies. These developments have introduced new notions of identity and behavior in the digital space. This article adopts a socio-conceptual approach, grounded in Marc Prensky’s concept of the “digital native,” to examine digital citizenship as a set of behaviors and standards guiding ethical, responsible, and safe technology use. It highlights key dimensions and challenges of digital citizenship, particularly amid the strong influence of social media on youth. The article concludes with practical recommendations to encourage conscious and constructive engagement on digital platforms.